(untitled) (American Journal of Islam and Society, 2009)
A shortened version of his 2005 Habilitation thesis at Humboldt University, Berlin, this ambitious book both leans on and disagrees with German philosopher JürgenHabermas, the authoritative western theorist on the public sphere and communicative action. Salvatore applauds how Habermas created an original synthesis between the idea of civil society developed in the Anglo- American tradition and the more radical version of “civic virtue” in the European republican tradition emanating from Immanuel Kant. Habermas has masterfully wedded his theories of the public sphere and communicative action in such a way that “the only secure way to vindicate public reason is identified with a democratic process” (p. 240). A great achievement, no doubt, but at what cost? Salvatore sees this theory of the public sphere as condemned to an impasse. The “Habermas effect” has three main weaknesses: (1) it ultimately rests on the shaky ground of private trust; (2) its theory is limited to a western view of the self and citizenship and, in the end, to the reach of a hegemonic western culture; and (3) this limitation leaves out the all-pervasive dynamic of religious traditions in most other parts of the world ...